EDUKASI GIZI BALITA PADA IBU NIFAS DI DESA TEGAL SARI WILAYAH PUSKESMAS WALANTAKA SERANG BANTEN - Umalihayati Umalihayati; Qonita Qonita (STAI Darul Qalam Tangerang, 2023)
Nutrition is still a major problem in Indonesia, so that it can lead to serious nutritional problems. Nutrition is one of the assessment indicators to determine the degree of public health in Indonesia. Good nutrition can increase the productivity of human resources. Toddlers who experience nutritional disorders have an impact on stunting and underweight. On the other hand, if the child is over-nourished, then the child can experience obesity and other diseases such as diabetes mellitus. The contributing factor is the lack of knowledge of mothers about healthy menus and how to process food. The solution taken is to provide health education to the community in the form of health counseling. This activity aims to increase mothers' knowledge about toddler nutrition. Community Service will be held in September 2021 in Tegal Sari Village, Walantaka District, Serang City, Banten. Respondents who took part in the activity were 30 mothers with toddlers. This activity consists of 3 stages, including: the preparation stage, the implementation stage and the evaluation stage. Data obtained from the results of interviews, pre-test, post-test, and discussion. The result of this activity is an increase in mother's knowledge about toddler nutrition. Pre-test results, lack of knowledge 63.3% and 36.7% good. The results of the post test showed a change, namely 30% less knowledge and 70% good knowledge